Sorptivity Analysis of Lightweight Concrete Based on Fly Ash and Bottom Ash - Prasyanthi, Dian; ., Saloma; Aminuddin, Kiagus Muhammad (International Journal of Membrane Science and Technology, 2023)
Lightweight concrete has a density lower than conventional concrete, which ranges between 1,400-1,800 Kg/cm3. The use of lightweight concrete as a more sustainable construction material continues to be developed to reduce the weight of the building. Fly ash as a residue from coal combustion has a high SiO2 content as a cement substitute. Bottom ash with a light density can also be used as a substitute for fine aggregate. Sorptivity test in lightweight concrete aims to determine concrete's ability to absorb water and how the pores in concrete behave. Sorptivity testing was carried out by a 5x5x5(cm3) mortar sample that was immersed in water. Then the mortar was weighed based on time intervals of 1, 5, 10, 20, 30, and 60 minutes, then continued for 2, 3, 4, 5, and 6 hours and 1, 2, 3, 4, 5, 6, 7, and 8 days. The results showed that the use of fly ash and bottom ash could increase the sorptivity value in the mortar up to 0.45%, where the function of the fly ash and bottom ash is to fill the pores in the mortar so that the water content that seeps into the mortar is reduced. Thus, the use of fly ash and bottom ash to support ecologically friendly and lighter building results in more sustainable material properties.